Language as Worldbuilding in Genshin Impact : Non-translation of Finnish Elements - Cederqvist, Oskari (My University, 2026)
This thesis examines the role of non-translation in the English version of Genshin Impact, focusing on Finnish linguistic and cultural elements in the game’s Nod-Krai region. The aim of the study is to analyze how untranslated Finnish names and terms function within a localized video game and what effects they have on worldbuilding and cultural representation. The material consists of textual data collected from the official HoYoWiki website, including item descriptions, place names, character names, and lore-related content. The study applies a qualitative and descriptive approach, drawing on key concepts from translation studies and game localization research. The analysis shows that Finnish elements are retained across multiple layers of the game, including mythological names, adapted terms, place names, food items, and NPC names. These untranslated elements do not prevent comprehension but instead contribute to the distinct identity of the region. The findings suggest that non-translation can function as a deliberate strategy in video game localization. Rather than reducing accessibility, it can support player immersion and cultural specificity when meaning is reinforced through gameplay, visuals, and context.
Keywords: non-translation, videogame, localization